2019
DOI: 10.3892/ol.2019.10135
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A is a reliable proliferation marker in endometrial cancer cell lines

Abstract: Cyclin A, a cell cycle regulatory protein, promotes cell proliferation and has been observed to be highly expressed in cancer and to promote tumor growth; however, its value as a marker for endometrial carcinoma has not yet been established. Accordingly, the aim of the present study was to clarify whether cyclin A can be used as a cell proliferation marker using the endometrial carcinoma cell lines Ishikawa and HEC-50B, derived from patients with low-grade and high-grade cancer, respectively. The expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…Cyclin A depletion caused the reduction of DNA synthesis activity [ 31 ]. In addition, recent evidence suggests that cyclin A could be regarded as a proliferation marker [ 32 ]. Given our data showed that Fubp1 is a transcription activator of genes encoding cyclin A, we examined the role of Fubp1 in cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin A depletion caused the reduction of DNA synthesis activity [ 31 ]. In addition, recent evidence suggests that cyclin A could be regarded as a proliferation marker [ 32 ]. Given our data showed that Fubp1 is a transcription activator of genes encoding cyclin A, we examined the role of Fubp1 in cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…USP7 might also contribute to oncogenesis by deubiquitinating and stabilizing Ki-67 ( Zhang et al, 2016 ). As with Cyclin A2, Ki-67 is highly expressed in malignant tissues and promotes cell division ( Sales Gil and Vagnarelli, 2018 ; Horie et al, 2019 ). This interaction may be particular disease-relevant in non-small cell lung cancer cells, where a strong positive correlation between the two proteins has been observed ( Zhang et al, 2016 ).…”
Section: Usp7: Links With Cancermentioning
confidence: 99%
“…D9 caused significant decreases in cyclin D1, indicating the growth inhibitory effects on cyclin D1 of D9 (Figure C–E). Besides, the cyclin B1 and CDK1 complex plays crucial roles in regulating the transition from the G2 to the M phase and the expression of cyclin A, which promotes both cell cycle G1/S and G2/M transitions . We discovered that D9 increased the protein levels of cyclin B1, CDK1 and cyclin A in a concentration‐dependent manner (Figure C–E).…”
Section: Resultsmentioning
confidence: 78%